PERAN PERGURUAN TINGGI MENGHADAPI DISRUPSI PERADABAN - I Ketut Widnya (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
Disrupsi initiated the birth of a new business model with a more innovative creativestrategy. The scope of change is broad ranging from the world of business, banking, transportation,socialsocietytoeducation.Thiserawillrequireustochangeorbecomeextinct.Innovateorlag.Nodoubtdisruptionwillencouragethedigitalizationoftheeducationsystem.TheemergenceoftechnologicalapplicationinnovationssuchasUberorGojek,Grabandotherswillinspirethebirthofsimilarapplicationsinthefieldofeducation.Teachingandlearningactivitieswillchangecompletely.Classroomsexperienceevolutionwithdigitallearningpatternsthatprovideamorecreative,participatory,diverseandcomprehensivelearningexperience.